Current conceptual challenges in the study of rhythm processing deficits - Tranchant, Pauline; Vuvan, Dominique T. (Frontiers in Neuroscience, 2015)
Interest in the study of rhythm processing deficits (RPD) is currently growing in the cognitive neuroscience community, as this type of investigation constitutes a powerful tool for the understanding of normal rhythm processing. Because this field is in its infancy, it still lacks a common conceptual vocabulary to facilitate effective communication between different researchers and research groups. In this commentary, we provide a brief review of recent reports of RPD through the lens of one important empirical issue: the method by which beat perception is measured, and the consequences of method selection for the researcher’s ability to specify which mechanisms are impaired in RPD. This critical reading advocates for the importance of matching measurement tools to the putative neurocognitive mechanisms under study, and reveals the need for effective and specific assessments of the different aspects of rhythm perception and synchronization.